Treatment of pharmaceutical wastewater by advanced oxidation process (AOP) - Chelliapan, Shreeshivadasan; Sallis, Paul (2008)
Advanced oxidation process (AOP) is defined as aqueous phase oxidation processes which are based primarily on the intermediacy of the hydroxyl radical in the mechanism resulting in the destruction of the target pollutant. AOP have been applied to refractory organic pollutants and xenobiotics found in industrial wastewater to improve biodegradability and also increase treatment efficiency. Numerous researchers have evaluated on the treatment of refractory compounds by different AOP processes. However, few studies reported in the literature dealt with pharmaceutical effluents. In this paper, studies of the further polishing of effluent from an aerobic reactor using different types of AOP was presented and discussed.